Only the Rye Derived Part of the 1BL/1RS Hybrid Centromere Incorporates CENH3 of Wheat - Karimi-Ashtiyani, Raheleh; Schubert, Veit; Houben, Andreas (Frontiers in Plant Science, 2021)
The precise assembly of the kinetochore complex at the centromere is epigenetically determined by substituting histone H3 with the centromere-specific histone H3 variant CENH3 in centromeric nucleosomes. The wheat-rye 1BL/1RS translocation chromosome in the background of wheat resulted from a centric misdivision followed by the fusion of the broken arms of chromosomes 1B and 1R from wheat and rye, respectively. The resulting hybrid (dicentric)centromere is composed of both wheat and rye centromeric repeats. As CENH3 is a marker for centromere activity, we applied Immuno-FISH followed by ultrastructural super-resolution microscopy to address whether both or only parts of the hybrid centromere are active. Our study demonstrates that only the rye-derived centromere part incorporates CENH3 of wheat in the 1BL/1RS hybrid centromere. This finding supports the notion that one centromere part of a translocated chromosome undergoes inactivation, creating functional monocentric chromosomes to maintain chromosome stability.